Shape optimization of an integrated mast for rcs reduction of a stealth naval vessel - Shin, Hokeun; Yoon, Daeyeong; Kim, Chanyeong; Yang, Young Sub; Lee, Man Gyu; Park, Joon Young; Hwang, Keum Cheol; Park, Yong Bae (Applied Sciences (Switzerland), 2021)
In this paper, we analyze the radar cross section (RCS) of an integrated mast and present the optimized mast shape for RCS reduction. The RCS is simulated using commercial electromagnetic (EM) software based on the shooting and bouncing rays (SBR) method and the diffraction fields at the edges are also considered. Threat frequencies, threat regions and cardinal points are first defined considering the operational environments of a naval vessel. We calculate and analyze the RCS of the integrated mast in terms of the threat frequencies, the shapes of the integrated mast and the direction and polarization of the incident waves. The shape of the integrated mast is optimized based on the shaping technique. The optimized mast has low RCS properties in the primary threat sectors except for the exceptional angle regions.
Keywords: Integrated mast; Naval vessel; Radar cross section reduction; Shaping technique; Stealth design